Trends in Deforestation as a Response to Management Regimes and Policy Intervention in the Hindu Kush Himalaya of Pakistan - Ahmad, Adnan; Ahmad, Shahid; Nabi, Ghulam; Liu, Qi-Jing; Islam, Nazirul; Luan, Xiaofeng (Frontiers in Environmental Science, 2022)
Based on the annual rate of deforestation as a forest conservation outcome, this study evaluated how effective is the existing forest-management regime in controlling deforestation in the study area. Remote sensing data was used to measure the rate of deforestation. Furthermore, the existing forests management regime in the study area, as well as in other regions of the Himalaya and Karakorum ranges of Pakistan and the Himalaya temperate biome of India, China, Nepal, and Bhutan, were reviewed to compare deforestation. Results showed that with regional-wise management regimes, the overall annual rate of deforestation was recorded much higher in the study area (0.8 yr-1) compared to the Himalaya and Karakoram ranges of Azad Kashmir (0.13 % yr-1), Punjab (0.20% yr-1), and Gilgit Baltistan (0.31% yr-1). The cross-national and site-regional findings highlighted that lowest deforestation was associated with management regimes characterized by effective monitoring and law enforcement with the inclusion of conservation and community. Deforestation was higher in forest management regimes that aimed to maximize economic growth, unstable rights, weak law enforcement, and exclusion of conservation and community-based management/use. In conclusion, the best forest conservation outcomes are associated with management regimes that include conservation and community, stable and secure rights supported by high-ranking monitoring and law enforcement. Therefore, the inclusion of community and conservation supplemented with stable rights and high-rank monitoring and law enforcement into the existing management regimes are suggested.